(untitled) (Law and world, 2015)
This article is a pioneering scientiﬁc work at the intersection of natural human sciences, which aim is to ensure sustainable peace and prevent global economic, political, social and legal disorder under the aegis of the Bill of Human Rights. The proposed theory oﬀ ers a new mechanism for overcoming existing disorders and preventing new disorders, and in the end – to open the door “to merge into the orders of order” (Shota Rustaveli XII c.). The author has a noble goal to provoke the colleagues from diﬀerent disciplines to participate in the building of bridges between the economic, political, social and legal sciences for properly “ﬁtting” humanity in harmony with natural normative order. The paper serves as a fruitful source of new ideas for students, researchers and professionals working in the ﬁeld of physics, biology, anthropology, economics, politics, sociology, jurisprudence, or related ﬁelds.